2021
DOI: 10.3389/fgene.2021.721949
|View full text |Cite
|
Sign up to set email alerts
|

A Network-Based Methodology to Identify Subnetwork Markers for Diagnosis and Prognosis of Colorectal Cancer

Abstract: The development of reliable methods for identification of robust biomarkers for complex diseases is critical for disease diagnosis and prognosis efforts. Integrating multi-omics data with protein-protein interaction (PPI) networks to investigate diseases may help better understand disease characteristics at the molecular level. In this study, we developed and tested a novel network-based method to detect subnetwork markers for patients with colorectal cancer (CRC). We performed an integrated omics analysis usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 84 publications
2
7
0
Order By: Relevance
“…It has been tested in the studies of various diseases, including cancer, schizophrenia, and postpartum hemorrhage 16 20 . Regarding UC, the characteristics of high stability and prediction accuracy of the SVM method have also been proven in previous reports 21 , 22 . Another method of ML, the Least Absolute Shrinkage and Selection Operator (LASSO) analysis, is commonly used in the biomarker identification of various carcinoma diseases 23 25 .…”
Section: Introductionsupporting
confidence: 54%
“…It has been tested in the studies of various diseases, including cancer, schizophrenia, and postpartum hemorrhage 16 20 . Regarding UC, the characteristics of high stability and prediction accuracy of the SVM method have also been proven in previous reports 21 , 22 . Another method of ML, the Least Absolute Shrinkage and Selection Operator (LASSO) analysis, is commonly used in the biomarker identification of various carcinoma diseases 23 25 .…”
Section: Introductionsupporting
confidence: 54%
“…Indeed, the previous studies, including our own, reported that the multiomics approach may increase the robustness and reliability of biomarkers associated with complex diseases, including cancer (Miao et al, 2014;Aldosary et al, 2020;Das et al, 2020;Al-Harazi et al, 2021a;Baloni et al, 2021;Kaya et al, 2022;Ruan et al, 2022). Additionally, it has been reported that networkbased approaches have high efficacy in identifying biomarkers for many complex diseases, including several different types of cancer (Wang et al, 2017;Chen et al, 2019;Liu et al, 2019;Uddin et al, 2019;Khan et al, 2020;Al-Harazi et al, 2021b). However, most biomarkers identified thus far require invasive procedures.…”
Section: Introductionmentioning
confidence: 94%
“…First, we used the GSE23878 dataset for building the classification model, and then tested the classification performance on an indepedent dataset (TCGA dataset) to confirm if the 17-gene-classifier can distinguish patients from normal controls. We evaluated the performance of the classifier for its accuracy, specificity, sensitivity, and area under curve (AUC), as described previously (Al-Harazi et al, 2021a;Al-Harazi et al, 2021b). The analyses were performed using PARTEK Genomics Suite (Partek Inc., St. Lois, MO, United States).…”
Section: Colorectal Cancer Classifier Model and Performance Evaluationmentioning
confidence: 99%
“…Thus, protein interactions and their networks are very important in most biological functions and processes [ 5 ]. Protein interaction networks can help us better understand the disease process, which is of great significance in the identification of disease proteins/gene [ 6 , 7 ]. Roudi et al identified differentially expressed genes (DEGs) at each stage of lung adenocarcinoma in four datasets from the Gene Expression Omnibus (GEO) database.…”
Section: Introductionmentioning
confidence: 99%